Tatak Pilipino [episode no. 86][videorecording]. ([Quezon City ABS-CBN], 1992)
Summary: A unique display of Pilipino ways and style.
Contents: Tilapia (5 min.) -- Magnetic Hill in U.P. Los Banos, Laguna (10 min.) -- T'boli orthodontics (5 min.) -- Pag-ihi sa kalye (5 min.) -- Exotic food (8 min.) -- Rose dishes (2 min.) -- Jeepneys (5 min.).
Credits: Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Tilapia; Food; Jeepneys; Sanitation -- Philippines; T'bolis.; Magnetic Hill (Laguna).; Home economics; Philippine history; Agriculture; Geography